Palliative care nurse specialists' understanding and management of suffering and their individual response to working with patients who are suffering: An investigation. - Heather Margaret Davies (2007)
This thesis describes a study to explore palliative care nurse specialists' understanding and management of suffering and the personal impact of working with patients who are suffering. Background to the Study, Suffering is the individual's response to circumstances that befall them and arc perceived to have a negative impact. Nurses aim to help patients integrate suffering into their lives, which requires a deep understanding of the patient. Palliative care can be a very difficult area of work. Arguably, what suffering means to palliative care nurses will determine the focus and practical aspects of their care, further it may influence their personal responses. The Methodology, The study was guided by the ideas of hermeneutic phenomenology. Thirty one palliative care clinical nurse specialists working in south and mid Wales were interviewed to determine their understanding and management of suffering and their personal response to working with patients who are suffering. Semi-structured interviews enabled the exploration of their experiences and views. The data was analysed using the principles of phenomenological interpretation. The Findings of the Study, The palliative care nurse specialists had difficulty articulating the concept of suffering but their descriptions, often using clinical scenarios, mirrored the literature. Their understanding of suffering influenced their care management, in particular the nurse-patient relationship. Theoretical perspectives of suffering and person centred care were demonstrated and used to underpin care, although this had been learnt experientially. Development of understanding, knowledge and skills to manage suffering influenced their own responses to working with patients. They had developed a personal philosophy towards their work and positive reappraisal to cope with the stresses that arose. Conclusion, Clear links between understanding suffering, management of the nurse-patient relationship and the personal impact of working with patients who are suffering were demonstrated, as well as the role of experiential learning. Education about suffering and clinical mentorship may enable palliative care nurses develop skills and knowledge in both the care of patients who are suffering and their own ability to cope.